Everybody ease - reaching out to vulnerable subgroups of young people with mental health problems in the Netherlands: an adaptation of the standard @ease working method - Crombach, Casper; Janssen, S. E. R.; Daemen, Maud; Klaassen, R. M. C.; van Amelsvoort, T.; Leijdesdorff, S. M. J. (Child psychiatry & human development, 2025)
Young people with mental health problems do not always receive appropriate care. This study aims to increase understanding of the barriers and facilitators that young people face in their pathways towards care, by making use of targeted outreach activities by ease, a youth-friendly walk -in center in the Netherlands. A questionnaire enquiring demographic characteristics, symptom levels and levels of functioning was administered to young people as part of a pilot-outreach program at @ease. Semi-structured interviews were conducted with participants to explore their attitudes towards and experiences with mental health care and how these influenced their help-seeking. Sixty-six participants were included in the pilot-outreach @ease program. Main themes concerning participant help-seeking were ‘beliefs about self and others’, ‘accessibility of care’, ‘social network’ and ‘previous experiences with mental health care’. Participants also gave suggestions for care improvement. The outreach pilot successfully reached young people previously underrepresented through the regular @ease program. A key finding is that participants’ previous experiences with mental health care played an important role in shaping their attitudes towards future help-seeking for mental health problems, influencing them both positively and negatively.
Online veröffentlicht: 23 May 2025
Gesehen am 22.10.2025